WORD FORMATION IN SHARENA DELON’S INSTAGRAM POSTS: A MORPHOLOGICAL ANALYSIS - Crisnova Katalonika Siahaan (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2020)
This paper is a qualitative descriptive research which investigates the processes of word formation and their influence to part of speech of the data. The data source in this study is Instagram captions of Sharena Delon. The method of collecting data is by observation. The method of analyzing data is agih and padan method from Sudaryanto. The author uses the theory ofO’Grady which divides word formation process into 10 types, i.e.derivation, compounding, conversion, clipping, blends, backformation, acronym, onomatopoeia, coinage, and inflection. The research uses the theory of Carter & McCarthy to show the change of part of speech of data. The result of this research shows that based on O’Grady’s and Carter & McCarthy’s theory. There are 30 types of word formation process found in Instagram of Sharena Delon. Three types are by derivation process, 2 types by compounding process, 2 types by conversion process, 6 types by clipping process, 6 types by blends process, 2 types by backformation process, 3 types by acronym process, 3 types by onomatopoeia process, 1 type by coinage process, and two types by inflection process. Some data have change of part of speech because of word formation process and some do not.